Rotativa : Uma exposiçao de arte contemporânea em dois atos. (São Paulo : Galeria Fortes Vilaça, 2002)
Varejao, Adriana ; Milhazes, Beatriz ; Ferro, Chelpa ; Smith, Courtney ; Almeida, Efrain ; Neto, Ernesto ; Marcaccio, Fabian ; Ackermann, Franz ; de Espirito Santo, Iran ; Tschäpe, Janaina ; Hernández-Diez, José Antonio ; Damasceno, José ; Sarmento, Julião ; Roberts, Julie ; Catunda, Leda ; Barreto, Lia Menna ; Los Carpinteros ; Zerbini, Luiz ; Pape, Lygia ; Dias, Mauricio ; Riedweg, Walter ; Piva, Mauro ; Vaisman, Meyer ; Ramos, Nuno ; Neuenschwander, Rivane ; Guimaráes, Cao ; Renno, Rosângelo ; Cemin, Saint Clair ; Carneiro da Cunha, Tiago ; Soares, Valeska ; Muniz, Vik
biog., geselect. ind. tent., geselect. gr. tent. p. 74-83
Portugees & Engels
Rotativa, Galeria Fortes Vilaça, São Paulo, Fase 1 de / from 6.12.01 - 18.1.01 ; Rotativa Fase 2, 24.1.02 - 9.3.02
boek